Analisis Penerapan Hifz Al-Mal dalam Sistem Transaksi Berbasis Koin Kayu di Wisata Pasar Kebbun - Dela Elisia Putri; Subairi Syamsuri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the implementation of the wooden coin transaction system at Pasar Kebbun tourist market. The research employed a descriptive qualitative approach using observation, interviews, and documentation as data collection methods. The informants consisted of market managers, traders, and visitors who were directly involved in the transaction process. The findings indicate that the wooden coin system is implemented through a mechanism in which visitors exchange cash for wooden coins that serve as the primary means of payment within the market. This system provides several benefits, particularly for traders, as transactions become simpler, more standardized, and more efficient in calculating sales revenue. For visitors, the use of wooden coins creates a unique shopping experience while helping them manage and control their spending during their visit. Furthermore, the system contributes to more organized transactions and facilitates transaction management within the market environment. The main challenge identified is the initial difficulty experienced by some visitors in understanding and adapting to the wooden coin mechanism. However, this challenge does not result in significant financial losses and can be addressed through adequate information provided by market management. Overall, the wooden coin transaction system supports transaction orderliness, enhances economic efficiency, and aligns with the principle of Hifz al-Mal, which emphasizes the protection and responsible management of wealth in accordance with Islamic principles.